(untitled) (Research, Society and Development, 2021)
Juridical Psychology, considered a discipline still under construction, has been increasingly used in the legal field. The present work refers to a theoretical review on the theme of socio-affective parenting, seeking to know the criteria involving the definition of psychology professionals and their position regarding this reality in the legal environment, identifying possible interventions of the psychologist in situations involving the thematic. The methodology of this research encompasses a literature review with a narrative approach, considered a relevant theoretical foundation for the composition of articles, dissertations, theses, as well as course completion works. The results of the research pointed out the importance of the work of legal psychology nowadays, especially with regard to Family Law and its resulting changes in relation to the definition of multiparenthood. As a result of changes in the judicial system, the word affection was emphasized, taking into account the real bonds and going beyond genetic affiliation. Thus, there is a clear need for Psychology to develop tools and interventions aimed at this new reality that presents itself in the contemporary legal context.